Association of bmpr-1b gene 3"-utr region polymorphism with litter size in tibetan sheep - Jianlei JIA; Dejuan XIE; Yingying ZHANG; Huaixia ZHANG; Liping ZHANG; Shengzhen HOU; Qian CHEN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
Bone Morphogenetic Protein Receptor-1B (BMPR-1B) is considered as the primary gene in sheep for follicular development and litter size trait. It has been defi ned as the most major candidate gene for genetic markers of sheep reproductive performance. In our study, polymorphisms in the BMPR-1B gene 3"-UTR region were investigated in 363 Tibetan sheep (119 Plateau-type Tibetan sheep, 141 Valley-type Tibetan sheep, and 103 Oula-type Tibetan sheep) by DNA sequencing analysis. Two single nucleotide polymorphisms (SNPs) were identifi ed, which were G1339A and A1354G. The frequencies of SNPs were in Hardy-Weinberg equilibrium (Chi-square test, P>0.05). AA and AG genotypes were found in the A1354G variant of the 3"UTR region, that AA and A were the preponderant genotype and allele, respectively. The χ2 independence test analyses indicated that the A1354G variant of BMPR-1B gene 3"UTR region polymorphisms was signifi cantly correlated with litter size in all-types Tibetan sheep (P<0.05). These results demonstrate that the BMPR-1B gene 3"-UTR region might be a potential candidate gene for marker-assisted selection (MAS).